Antimicrobial coating with organic acids and essential oil for the enhancement of safety and shelf life of grape tomatoes - Jin, Tony Z.; Fan, Xuetong; Mukhopadhyay, Sudarsan (International journal of food microbiology, 2022)
This study investigated the antimicrobial efficacy of two coatings against populations of nalidixic acid-resistant Salmonella, Listeria monocytogenes and native microorganisms on whole grape tomatoes. Tomatoes were surface-coated in two chitosan-acid coating solutions. Solution 1 (Chitosan) consisted of 1 % chitosan and 2 % acetic, lactic and levulinic acids. Solution 2 (Chitosan+AIT) consisted of Solution 1 plus 2 % allyl isothiocyanate (AIT). After the treatments, tomatoes were placed in PET containers and stored at 10 °C for 21 days. Chitosan and Chitosan+AIT treatments reduced Salmonella populations from 3.65 to 1.28 and <0.70 log CFU/tomato on day 1, respectively. Both treatments reduced Salmonella populations to undetectable levels (<0.70 log CFU/tomato) from Day 2 through Day 21. Similarly, Chitosan+AIT treatments caused a greater reduction in Listeria populations than Chitosan treatment on day 1, but there were no significant differences between the two treatments after day 2. Chitosan and Chitosan+AIT reduced native bacteria populations to an undetectable level after 2 days and reduced the population of native yeasts & molds to an undetectable level after 1 day. The presence of mold was only observed on control sample after 21 days. Quality analyses showed that samples which were subject to coating treatment maintained their texture and color for 21 days at 10 °C with less water loss compared to the controls. This study suggests that chitosan-acid coating is applicable for extending the shelf-life and enhancing the safety of grape tomatoes. •Edible chitosan coatings with acids and allyl isothiocyanate were developed•Coating treatments reduced Salmonella and Listeria monocytogenes on grape tomatoes•Coating treatments maintained quality of grape tomatoes for 21 days at 10 °C